On the flow velocity of the ice sheet along the traverse route from Syowa to Mizuho Station, East Antarctica - Shibuya, Kazuo; Ito, Kiyoshi (1983)
P(論文) The 21st Japanese Antarctic Research Expedition (JARE-21,1979-1981) made several explosion seismic experiments by installing seismic stations along the S-H-Z route from Syowa to Mizuho Stations, on which JARE-14 (1972-1974) had made the traverse survey. Most of the seismic stations were selected to be closely located near the traverse stations, so that the position of each traverse station could be determined from that of a nearby seismic station determined by the NNSS positioning. By comparing the positions of selected traverse stations thus determined in 1980 with those determined in 1973,the flow velocity of the ice sheet along the S-H-Z route was estimated. Since the method of positioning and the referred geodetic coordinates by JARE-21 were not identical with those by JARE-14,several assumptions were made in the data reduction procedure and in the estimate of the flow velocity. The obtained magnitude of flow in 1973-1980 ranges from 108m with 290° flow direction at S27-3 to 475m with 267° flow direction at Z2 with the uncertainty of at most±14% for the flow value and ±13°for the flow direction. The change of the height at each traverse station ranges from -3.5m at H17 to +8.8m at H253 with about 10m uncertainty. Topographical features of the obtained flow velocity are discussed in view of the comparison with previously obtained flow velocity, the flow lines deduced from the surface topography, the strain field measured near the route and the free-air gravity anomalies over the Mizuho Plateau. departmental bulletin paper